RECLAMATION OF PLANT WASTES (STRAW) AND OBTAINING (NANO) CHIPS WITH BACTERICIDAL PROPERTIES BASED ON THEM - Leonidovna, Voropaeva Nadezhda (GeoScience Engineering, 2015)
Rape, camelina, wheat and Jerusalem artichokevegetable wastes (straw) as annually renewable raw materials were processed into activated carbons, which were modified with silver nanoparticles for carbonaceous sorbents to acquire specific properties, since carbonaceous sorbentsare usually widely used in the food industry, agriculture, medicine and other fields of human activity. The technology to obtain active carbons from agricultural crop residues has been developed, active carbon physico-chemical and adsorption properties, textural characteristics have been studied, new functional carbon (nano) materials with antibacterial activity containing (nano) particles of silver have been obtained, their influence within (nano) chip composition on rape crop growth, development and yield has been studied.